Dioscorea medusae (Dioscoreaceae), a new species from Espírito Santo, Brazil - Fraga, Fernanda Ribeiro De Mello; Couto, Ricardo Sousa; Braga, João Marcelo Alvarenga (Phytotaxa, 2019)
We describe here Dioscorea medusae, a new species that occurs in rupicolous plant communities on rocky outcrops (inselbergs) in northwestern Espírito Santo State, in Southeastern Brazil. This new species is markedly different from all species of Dioscorea from the Neotropic and it differs by its numerous short racemes, and flowers with three stamens and conspicuous anthers. We provide here a morphological description of the new species, notes on its habitat, distribution and phenology.